Linking Conservation, Equity and Poverty Alleviation: Understanding profiles and motivations of resource users and local perceptions of governance at Bwindi Impenetrable National Park, Uganda - Twinamatsiko, Medard; Baker, Julia; Harrison, Mariel; Shirkhorshidi, Mahboobeh; Bitariho, Robert; Wieland, Michelle; Asuma, Stephen; Gulland, E.J. Milner; Franks, Phil; Roe, Dilys (International Institute for Environment and Development, 2014)
Biodiversity conservation that contributes towards poverty alleviation is a priority under the 2011–2020 Strategic Plan for the Convention for Biological Diversity (CBD). Protected areas are important for CBD signatories to deliver this objective and the 10th Conference of Parties encouraged members to ‘support initiatives on the role of protected areas in poverty alleviation’ (Decision X31). Integrated Conservation and Development (ICD) has been promoted as an approach to conserve protected areas by addressing local development priorities. Although there have been successful ICD interventions, many that focus on reducing rural poverty have been criticized for failing to reduce threats to protected areas, often because the drivers of biodiversity loss and costs of conservation for local people are not fully understood
Keywords: Protected Areas; Resource use; Livelihoods; Bwindi Impenetrable National Park; Uganda; Equity